ANALISIS RASIO UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH KOTA SAMARINDA TAHUN 2014-2016 (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This study is aimed to analyse financial performance of Samarinda local government for period of 2014-2016 which is focused on ratio of effectiveness, ratio of financial efficiency, ratio of matchness, ratio of growth, and ratio of financial independence.This study is designed as quantitative descriptive. The study was held in Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) of Samarinda Government. Data was collected using documentation method. Technique of analysis which was used in this study was quantitative descriptive using formulas of ratio of effectiveness, ratio of financial efficiency, ratio of matchness, ratio of growth, and ratio of financial independence. The results of the analysis show that the financial performance of local government city of samarinda in terms of the ratio of the effectiveness of the original income areas categorized not as effective with an average effectiveness of 70%. financial efficiency ratios of the region belongs to inefficient because of the magnitude of the average of this ratio was 107.14%. the ratio of harmony can be categorized that local government is allocating most of the samarinda city budget budget submission for operational expenditure areas with average sevesar 63.18% compared with an average of capital expenditures that of 36.17%. the ratio of growth decline each year with an average of 1.15% less well categorized. the ratio of the financial independence of the area is still classified as low and instructive relationship patterns within the category because the average ratio of 20.54%.